1993
DOI: 10.1007/bf00237782
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and gonadotropin secretion after acute exercise in physically active males

Abstract: Serum concentrations of luteinizing hormone (LH), follicle stimulating hormone, testosterone (T) and melatonin were measured in seven physically active male volunteers after exercise on a treadmill using the Bruce protocol. Measurements were made on blood samples obtained before exercise, within 30 s after exercise, at 15 min after exercise, and subsequently at 30-min intervals after exercise for a total duration of 180 min. Serum LH concentration fell from a peak post-exercise level of 15.7 (4.7) IU.l-1 [mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…In view of the above links between melatonin, exercise, and the sympathetic nervous system, the acute responses of melatonin to exercise have been examined previously, but the findings of these studies are conflicting (Atkinson et al 2007). Previous researchers have reported an increase (Carr et al 1981;Ronkainen et al 1986;Skrinar et al 1989;Theron et al 1984), a decrease (Monteleone et al 1990), and no change (Elias et al 1993) in melatonin concentrations after exercise.…”
Section: Introductionmentioning
confidence: 90%
“…In view of the above links between melatonin, exercise, and the sympathetic nervous system, the acute responses of melatonin to exercise have been examined previously, but the findings of these studies are conflicting (Atkinson et al 2007). Previous researchers have reported an increase (Carr et al 1981;Ronkainen et al 1986;Skrinar et al 1989;Theron et al 1984), a decrease (Monteleone et al 1990), and no change (Elias et al 1993) in melatonin concentrations after exercise.…”
Section: Introductionmentioning
confidence: 90%
“…However, the report that physical activity did not cause any change in the melatonin levels of female athletes 14 is consistent with the melatonin levels we found both at rest and after exercise during the day. Similarly, in a study conducted on 7 male volunteers, no significant change was found in the melatonin levels measured in blood samples collected in four rounds: before exercise, 30 seconds after exercise, and 15 and 30 minutes after exercise 15 . This is a significant report lending support to the results we obtained with daytime exercise.…”
Section: Discussionmentioning
confidence: 83%
“…Various studies report that melatonin levels decrease, increase or remain unaffected by physical activity [44][45][46][47][48][49][50]. This variability in melatonin response to exercise can be explained by time of day, light conditions, type, duration or intensity of exercise, and by melatonin sampling scheme.…”
Section: Melatoninmentioning
confidence: 99%